Tantangan utama preservasi naskah kuno berbasis digitisasi - Testiani Makmur; Dudung Abdurahman; Sri Rohyanti Zulaikha; Dafrizal Samsudin (Perpustakaan Universitas Gadjah Mada, 2024)
Introduction. This research aims to determine the main challenges in preserving ancient manuscripts based on digitization. Research methods. This study used descriptive qualitative method. Data was obtained through literature studies based on scientific works published from 2013 to 2023. A total of 76 scientific works consisting of theses, national and international journals were obtained from the Google Scholar database with the keywords Naskah Kuno”, “Pelestarian Naskah Kuno”, “digitisasi naskah kuno.” Meanwhile in English it is like